How Costly is Tax Avoidance? Evidence from Structural Estimation - McClure, Charles G. (The Accounting Review, 2023)
ABSTRACT I develop a structural model to quantify the costs of tax avoidance. In the model, the firm trades off tax savings with tax audit risk, financial reporting considerations, and operational frictions imposed by tax avoidance, the last of which I label as nontax costs. The estimated parameters suggest nontax costs, which are difficult to observe, decrease pretax income by 6.4 percent or $58 million per firm-year. The large magnitude of this estimate can explain why firms appear to underutilize tax avoidance strategies. Through counterfactual analysis, I estimate the effect of tax audit risk and financial reporting considerations to find that financial reporting considerations have an effect on tax avoidance similar to the penalties imposed by tax authorities. Overall, the estimated parameters help explain the “undersheltering puzzle.” JEL Classifications: G14; H21; H25; H26; M41; M48.